A experiência educativa da extensão na Faculdades EST analisada sob a perspectiva da hermenêutica feminista - Paixão, Márcia Eliane Leindcker da (Universidade do Vale do Rio dos Sinos, 2011)
This dissertation interprets educational experiences within the Extension program of the Faculdades EST and Gender relations, based on the perspective of feminist hermeneutics and methodology. The concepts of the indissociability of teaching,research and extension, are presented here according to the presuppositions of the Extension Forum. They bring with them the concepts of oppression, gender and patriarchy from the feminist theory in dialog with the concepts of social in-exclusion. The first part of the dissertation presents the methodological research path, the contexts and the concepts which cross each other in the study and show the complexity involved in the theme. Feminist hermeneutics is presented based on Ivone Gebara and Wanda Deifelt, highlighting feminist methodology. The notion of the quotidian and experience in dialog with the concept of to make think of Richard Senett is presented. The second part focuses on historical aspects of the University Extension Program and the concept of indissociability as the background for the dialog with the concept of Gender and Exclusion, bringing the interfacing of the feminist perspectives to the dialogical plot. The analysis with regard to indissociability and the relations of Gender in the context of EST is problematized by the feminist hermeneutics. The concept of captivity presented by Marcela Lagarde, disquiets the places and practices and shows the ambiguity of women?s actions in extension programs. The extension program presents itself as a zone of comfort and of reinforcement of the patriarchy. But it can also be a zone of rebelliousness, of creativity and of possibilities for the women. The conclusion is that there is a counterpoint between theory, methodology and practice which, based on different approaches which dialog and interact, makes possible other extension practices and sets apart new gender relations in the institution
Keywords: Extensão universitária; Ensino superior; Hermenêutica feminista; Mulheres; Faculdades EST; ACCNPQ::Ciências Humanas::Educação